Age-related differences in the intrinsic connectivity of the hippocampus and ventral temporal lobe in autistic individuals - Chen, Lang; Abate, Meghan; Fredericks, Mackenzie; Guo, Yuanchun; Tao, Zhizhen; Zhang, Xiuming (Frontiers in Human Neuroscience, 2024)
Although memory challenges in autistic individuals have been characterized recently, the functional connectivity of the hippocampus and ventral temporal lobe, two structures important for episodic and semantic memory functions, are poorly understood in autistic individuals. Moreover, their age-related differences in the functional connectivity associated with these two memory networks are unrevealed. The current study investigated age-related differences in intrinsic connectivity of the hippocampal and ventral temporal lobe (vTL) memory networks in well-matched ASD (n = 73; age range: 10.23-55.40 years old) and Non-ASD groups (n =74; age range: 10.46-56.20 years old) from the open dataset ABIDE-I. Our findings revealed reduced connectivity in ASD compared to Non-ASD peers, as well as an age-related reduction in the connectivity of hippocampal and vTL networks with triple networks, namely, the default-mode network (DMN), the central executive network (CEN), and the salience network (SN), potentially underpinning their challenges in memory, language, and social functions. However, we did not observe reliable differences in age-related effects between the ASD and Non-ASD groups. Our study underscores the importance of understanding memory network dysfunctions in ASD across the lifespan to inform educational and clinical practices.